Rise of ISIS and Security Implications for Middle East - Mr. Sajid Aziz (CISS Insight Journal, 2014)
ISIS’ juggernaut continues to gobble up more land in Syria and Iraq, expanding its ‘caliphate’ in territories it conquers. The besieged town of Kobani, a Syrian border town in close proximity to Turkey, is in the midst of a savage battle between ISIS and Kurds, the latter buttressed by American airpower and weapons. Routing its rivals the official al-Qaida affiliate, Jabhat al-Nusra and Ahrar al-Sham, ISIS took control of oil-rich province of Deir Ezzor in Syria, the oilfields from which gush out millions of barrels of oil, and the revenues collected from sale of oil from these oilfields bankroll its battles. Taking advantage of chaos and anarchy, Kurds in northern Iraq expanded their influence to Kirkuk. They already had autonomous regional status in Erbil, their capital, Halabja and Sulamaniya in northern Iraq. As the brutalities of ISIS in executing journalists and massacring people on sectarian basis gained notoriety, the governments in Syria and Iraq too accumulated infamy by dropping barrel-bombs indiscriminately on towns and cities under ISIS’ control. The resultant exodus of civilians in Syria has reached over 7 million, one of the largest refugee movements in recent history. At the regional level, this war has soured Turkey’s relations with Iraq, Iran and Syria. The last three believe Turkey, along with Saudi Arabia and Qatar to be the paymasters of the groups fighting in Iraq and Syria. This has led to sharpening of fault lines on religious and sectarian divide. Add to this Iran’s F-4 phantom fighters pounding ISIS positions in Iraq and America’s firefight in Syria. Hezbollah too has sent thousands of its guerillas to fight alongside Assad’s forces to halt the further advance of ISIS. This situation is messy at its worst.